Kemampuan Mahasiswa PGMI dalam Mengembangkan Soal Berbasis Literasi Sains - Bungawati; Rahmadani, Ervi (Jurnal Ilmu Pendidikan Dasar Indonesia, 2021)
This study aims to determine the ability of PGMI students in developing scientific literacy-based questions in science learning in MI/SD. The research method used is qualitative with descriptive analysis. The results of the study found that the ability of students to develop scientific literacy-based questions on the competency dimension was in the good category, the content dimension was in the good category, the science context dimension was in the very good category and the scientific attitude category was in the poor category. It can be concluded that the students' ability in developing scientific literacy-based questions is in the "good" category.